Prevention of mother to child transmission lay counsellors: Are they adequately trained? - Catherine H. Thurling; Candice Harris (AOSIS, 2012)
South Africa's high prevalence of human immunodeficiency virus (HIV) infected women requires a comprehensive health care approach to pregnancy because of the added risk of their HIV status. As a result of the shortage of health care workers in South Africa, lay counsellors play important roles in the prevention of mother to child transmission of HIV (PMTCT). There is no standardization of training of lay counsellors in South Africa, and training varies in length depending on the training organisation. The study aimed to investigate the training of lay counsellors by analysing their training curricula and interviewing lay counsellors about their perceptions of their training. A two phase research method was applied. Phase one documented an analysis of the training curricula. Phase two was semi-structured interviews with the participants. Purposive sampling was undertaken for this study. The total sample size was 13 people, with a final sample of 9 participants, determined at the point of data saturation. The research was qualitative, descriptive and contextual in design. The curricula analysed had different styles of delivery, and the approaches to learning and courses varied, resulting in inconsistent training outcomes. A need for supervision and mentorship in the working environment was also noted. The training of lay counsellors needs to be adapted to meet the extended roles that they are playing in PMTCT. The standardization of training programmes, and the incorporation of a system of mentorship in the work environment, would ensure that the lay counsellors are adequately prepared for their role in PMTCT.